Pengaruh Financial Literacy dan Financial Self-efficacy terhadap Keputusan Investasi pada Bursa Efek Indonesia (Studi Empiris pada Masyarakat Usia Produktif Pasar Saham di Kota Jambi) - Sari, Amilia Paramita (Universitas Batanghari Jambi, 2025)
This study aims to analyze the influence of financial literacy and self-efficacy on investment decisions on the Indonesia Stock Exchange (IDX) among the productive-age population in Jambi City. This research method uses a quantitative approach with multiple linear regression analysis. The research sample consisted of 100 respondents selected using a purposive sampling method with the criteria of productive-age individuals who have invested in the stock market and have experience attending investment-related education. Data were collected through a questionnaire that has been tested for validity and reliability. The results show that both financial literacy and self-efficacy have a positive and significant influence on investment decisions. These findings suggest that individuals with high levels of financial literacy tend to be more active in investing, while strong self-efficacy increases confidence in financial decision-making.